Development of a decision support model for optimization of tour time to visit tourist destination points in a city - Shrestha, Jagat Kumar (Geographical Journal of Nepal, 2017)
There may be a number of tourist destinations in a city; however, a tourist may have limited time that can be spent for tourism. The tourist may be interested to visit as many tourist destinations as possible in the limited time. In this situation, the tourists want to optimize their travelling time and moments of leisure, taking the opportunity to visit the desired city attractions. This paper proposes a decision support model for optimization of tour time to visit tourist destination points in a city which deals with edge removal from a network and searching for alternate short routes to optimize the total tour time.